2020
DOI: 10.1021/acs.biochem.0c00387
|View full text |Cite
|
Sign up to set email alerts
|

Cruciform DNA Sequences in Gene Promoters Can Impact Transcription upon Oxidative Modification of 2′-Deoxyguanosine

Abstract: Sequences of DNA typically adopt B-form duplexes in genomes, although noncanonical structures such as G-quadruplexes, imotifs, Z-DNA, and cruciform structures can occur. A challenge is to determine the functions of these various structures in cellular processes. We and others have hypothesized that G-rich G-quadruplex-forming sequences in human genome promoters serve to sense oxidative damage generated during oxidative stress impacting gene regulation. Herein, chemical tools and a cell-based assay were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
(291 reference statements)
0
10
0
Order By: Relevance
“…G-quadruplexes (G4) are secondary structures of guanine-rich nucleic acids that form a helical structure due to guanine: guanine interactions and are commonly seen in promoter regions, 5 and 3 untranslated regions, and within telomeric regions of DNA [54]. In addition to G-quadruplexes, oxidative DNA damage has also been shown to alter cruciform DNA sequences in the promoter elements of genes [55]. The formation of G4 and cruciform structures can enhance or repress the transcription of genes, depending on whether the secondary structure forms within the template or nontemplate strands [55,56], thus oxidation-induced increases in DNA secondary structures provide another means by which oxidative damage alters gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G-quadruplexes (G4) are secondary structures of guanine-rich nucleic acids that form a helical structure due to guanine: guanine interactions and are commonly seen in promoter regions, 5 and 3 untranslated regions, and within telomeric regions of DNA [54]. In addition to G-quadruplexes, oxidative DNA damage has also been shown to alter cruciform DNA sequences in the promoter elements of genes [55]. The formation of G4 and cruciform structures can enhance or repress the transcription of genes, depending on whether the secondary structure forms within the template or nontemplate strands [55,56], thus oxidation-induced increases in DNA secondary structures provide another means by which oxidative damage alters gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to G-quadruplexes, oxidative DNA damage has also been shown to alter cruciform DNA sequences in the promoter elements of genes [55]. The formation of G4 and cruciform structures can enhance or repress the transcription of genes, depending on whether the secondary structure forms within the template or nontemplate strands [55,56], thus oxidation-induced increases in DNA secondary structures provide another means by which oxidative damage alters gene transcription. Recent reports suggest that APE1 binding to AP sites within G4 sequences increases the folding of DNA into G4 structures and maintenance of APE1 binding, via APE1 acetylation, stabilizes the G4 and increases transcription factor recruitment to the promoter [29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cruciform DNA nanostructure is used for targeted delivery of doxorubicin to cancer cells [ 121 ] and was used to treat colon cancer [ 122 ]. It has also been demonstrated that cruciforms in gene promoters impact transcription upon oxidative modification of 2’-Deoxyguanosine [ 123 ]. The association of cruciforms with the regulation of transcription [ 90 ], as discussed above, opens other therapeutic windows where the specific levels of gene expression are influenced by the their presence and stability in promoter regions.…”
Section: Inverted Repeats and Cruciforms As Potential Therapeutics In...mentioning
confidence: 99%
“…Also, it is now clear that non-B-DNA structures are powerful determinants of mutagenesis [106]. There are an abundance of non-B-DNA structures [36], but those that are particularly relevant to gene promoter regions are G-quadruplexes [46,47], i-motifs [65,66], cruciforms [69], triplexes [107], and Z-DNA [108], as illustrated in Figure I. These local non-B-DNA structures are often targets of protein binding, including various transcription factors [109][110][111].…”
Section: Box 2 Non-b-dna Structuresmentioning
confidence: 99%
“…Other non-B-DNA structures shown to be important in promoters are hairpins and the cruciforms, which can be formed by inverted repeat sequences that are abundant in many genomes [34,36,69]. Hairpins and cruciforms serve as effective targets for several regulatory proteins, including transcription factors such as p53 and p73 [70][71][72].…”
Section: Promoter Structure Motifsmentioning
confidence: 99%